(untitled) (Journal of Nepal Geological Society, 1997)
The Upper Tertiary sandstones of the foothills of the Arunachal Himalaya, eastern India were studied to determine the depositional condition, provenance and tectonic framework of deposition of the sandstones. For this purpose, size analysis and mineralogical and basin configuration studies were carried out. The mineralogical composition of the sandstones indicates that the sandstones were mainly derived from the metamorphic and igneous rocks. The compositional study indicates that these immature sandstones were developed in the continental block provenance under humid climatic conditions affected by major tectonic disturbances. The sedimentological study shows that the sediments of the sandstones were waterlaid and deposited rapidly in the Arunachal basin, which was a shallow and fresh water basin and tectonically active at the time of sedimentation.